Synthesis of Digital Automatic Control System for Non-Transformer Step-Up Converter of Constant Voltage - A. V. Mironovich; P. P. Primshits (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper is devoted to investigation of semi-conductor pulse step-up converter of constant voltage which is operating in the boundary-continuous current mode of a choke with digital control. The algorithms that have been developed make it possible to calculate the given value of coke current and sustain its saw-shape form with the help of digital control device. Values of feed back coefficients have been calculated by object coordinates at discrete character concerning change of control action.The paper contains results of computer converter simulation in MATLAB model. The results prove that digital control with discrete period of 0.001 second can be implemented to step-up converter of constant voltage in the boundary-continuous current mode of a choke.